If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-3x=x+7
We move all terms to the left:
2-3x-(x+7)=0
We get rid of parentheses
-3x-x-7+2=0
We add all the numbers together, and all the variables
-4x-5=0
We move all terms containing x to the left, all other terms to the right
-4x=5
x=5/-4
x=-1+1/4
| (x+2)²=2x+7 | | y=6.3× | | x^2-3x-10.1=0 | | 14x+100=-7x-5 | | -2(3x+1)=-6x+2 | | 3(2w+9)=(5+w) | | 3(b-2=9 | | 6b+15=2b-9 | | 3y-(5y+8y)=4 | | 1/8=50/x | | 15=3x+1 | | u/1.5+2.7=7.7 | | 3(x-4)+5x=-8 | | 0=34.6x-5x^2 | | 2(n+2)+2=3n | | 2x+1=13;x=6 | | 0.5x-11.5=-7.5 | | 4(2x+3)-7=45 | | n(n-1)=206 | | (2x-1)^2+(2x+1)^2=130 | | 3e^2×-1=1/2 | | 4x^2+1=130 | | 6x+12=39-6x | | X^6-1.17x-0.16=0 | | 8x3-1/1-2x3=0 | | 4(5-x)=16 | | 12=25-3x | | -18+35x-16x^2=0 | | 2x(3x9)=(2x3)x9 | | ((2^3x-3)-10)/9=6 | | 9x=600 | | (2^3x-3-10)/9=6 |